2020
DOI: 10.30892/gtg.28117-464
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tourists’ Perceptions on Safety at the Cape Coast Tourist Destination in Ghana

Abstract: Ge eo oJ Jo ou ur rn na al l o of f T To ou ur ri is sm m a an nd d G Ge eo os si it te es s Year X

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
0
8
2
2
Order By: Relevance
“…In tourism academia, a study by (Chiciudean et al, 2019) has used resident's feelings of safety and security to determine the critical factors for sustainable rural development. In another study, researchers (Imbeah et al, 2020;Wang et al, 2010) reveals that female residents of the Chinese city of Shandong reported reluctance to embrace tourism due to safety and security concerns, which makes the construct even more vital for academic scrutiny, (Konstantaki and Wickens, 2010) corroborate the same through their findings among London residents which showed lack of confidence about the security arrangements made during the 2012 London Olympic Games. conceptualised the measure of "community gain" wherein one of the critical parameters is residents' perception towards community safety and security; their study aims to gauge the collective perception of the inscription of George Town in coastal Malaysia as a WHS.…”
Section: Literature Review Theoretical Framework and Constructsmentioning
confidence: 78%
See 1 more Smart Citation
“…In tourism academia, a study by (Chiciudean et al, 2019) has used resident's feelings of safety and security to determine the critical factors for sustainable rural development. In another study, researchers (Imbeah et al, 2020;Wang et al, 2010) reveals that female residents of the Chinese city of Shandong reported reluctance to embrace tourism due to safety and security concerns, which makes the construct even more vital for academic scrutiny, (Konstantaki and Wickens, 2010) corroborate the same through their findings among London residents which showed lack of confidence about the security arrangements made during the 2012 London Olympic Games. conceptualised the measure of "community gain" wherein one of the critical parameters is residents' perception towards community safety and security; their study aims to gauge the collective perception of the inscription of George Town in coastal Malaysia as a WHS.…”
Section: Literature Review Theoretical Framework and Constructsmentioning
confidence: 78%
“…Jurowski and Gursoy, 2004 differentiated their sample into 3 sub-samples based on a group's physical proximity to a World Heritage Site; the prediction indicated varying sentiments towards resource consumption among the groups. Imbeah et al, 2020 have argued that while residents are aware that resource duplicity exists in the use of resources among natives and tourists, further research should explore how this affects support for conservation.…”
Section: Literature Review Theoretical Framework and Constructsmentioning
confidence: 99%
“…For instance, tourists prefer bottled water to mitigate the potential adverse health risks (e.g. diarrhea, stomach ache) caused by drinking unsafe water, especially when travelling to adventure-based destinations such as Peru and Ghana (Bauer, 2012; Imbeah et al , 2020). Besides, considering the relatively high risk of theft during travel, tourists also receive advice from travel agencies and local authorities to protect valuables, such as hiding valuable items, using a money belt and carrying protection devices (Leggat and Klein, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Tourists are known to avoid certain destinations because they are considered unsafe. This antecedent of TS has been analysed in recent studies, including those by Buckley et al (2014), Imbeah et al (2020) and Lee et al (2010). All authors have highlighted the strong link between DS and perceived TS.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%